Determination of Audit Opinion Going Concern Moderating Role by Shares Return - Ajeng Farida; Putri Fariska (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Study This aims to know the influencing factors _ going concern audit opinion with the moderating variable stock returns that are influenced by the independent variable consisting of price book value (PBV), debt equity ratio (DER), and earnings per share (EPS). Sample study as many as 14 companies of agriculture listed on the ASEAN Stock Exchange during the period 2019-2021 with method taking sample use of purposive sampling. Data analysis using multiple linear regression and hypotheses tested by T-test with level significance 0.05. From the results analysis regression obtained, by simultaneous test show results price book value (PBV), debt equity ratio (DER), and earnings per share (EPS) have an effect positive to going concern audit opinion with moderation returns stock. The results study in a manner partial, only variable influential price book value (PBV) significant positive to going concern audit opinion with moderation returns stock. Where the variable debt-equity ratio (DER) and earnings per share (EPS) show that in a manner partial no influence to going concern audit opinion with moderation returns stock.